OPTIMALISASI LAHAN PEKARANGAN DENGAN BUDIDAYA TANAMAN HORTIULTURA DI KELURAHAN MAJENANG KECAMATAN SUKODONO KABUPATEN SRAGEN - Riyadi, Joko Sekti; Diva Awatara, I Gusti Putu (WASANA NYATA, 2018)
The utilization of yard land in Indonesia show that not been touched properly. Whereas if optimized, the use of yard can provide many advantages as a means to meet household needs and increase family income. The yards of the yard have potential in providing family food, reducing household expenditures for food purchases and increasing farm households. The number of obstacles related to social, cultural and economic problems are still found in the program of land utilization of the yard, such as not yet intensive cultivation of yard farming, it is still odd and not market-oriented and not optimal mentoring process.The purpose of this is to improve the skills of families and communities in the utilization of yard land, meet food needs and increase family income. This devotional activity is carried out in Majenang of Sukodono District Sragen Regency. Alternatives to the commodities grown are chili, tomatoes, eggplant, spinach, kale, mustard greens, and long beans.The results of this service show that members of Mekar Sari farmer group in Majenang of Sukodono district can increase in fulfilling family's foodstuff, reduce household expenditure for food purchase and increase farmers household income.Keywords: yard area, income, horticulture crop